Transformation of healthcare in developing countries by new generation technologies and analyzing tools. - Mohammad Serajuddin, Ali Akhtar, Amjad Khan, Zafrul Hasan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We are interested in explanatory strategies for coping with change in this study. In health units, the implementation of digital health technologies is of greater importance since the use of digital technologies helps to improve healthcare, knowledge transfer, and performance, particularly in developing countries and in achieving the Millennium Development Goals (MDGs). This paper seeks to identify the factors that influence the use of emerging technologies in the healthcare sector. Innovative technologies are being utilized to record processes and transactions efficiently. When it comes to staying competitive in the healthcare industry, healthcare providers have no choice but to embrace digital transformation. Cloud computing (CC), the Internet of Things (IoT), Artificial Intelligence (AI), and Big Data (BD) are a few areas where mobile applications play an important role. Technology needs to be accepted by those who must use it, and we must understand what factors make these systems successful so that we can improve implementation methods. Fundamental to public health and quality of care. Accordingly, these rationales indicate that digital transformation is currently being embraced by healthcare providers. The benefits of digital transformation are substantial for healthcare organizations. Reducing employee travel costs, reducing time away from patients, and reducing the time spent on information systems (IS) in the healthcare sector are all possible benefits